2009
DOI: 10.2340/16501977-0456
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic stimulation in constipation associated with Parkinson’s disease

Abstract: There was a statistically significant reduction in colonic transit time and in the questionnaire score following the intervention. The difference in the anorectal angles between resting and evacuating process and the changes in pelvic floor descent all reached significance after the intervention. The therapeutic effects that achieved significance remained constant in the 3-month follow-up result. Functional magnetic stimulation may facilitate colonic motility in Parkinson's disease and straighten the anorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 0 publications
1
26
0
3
Order By: Relevance
“…[202][203][204] EMST, which uses currentchanging magnetic fields, allows the induction of electrical stimulation in the desired deep tissue. The mechanism of EMST in the S2-S3 dermatomes for constipation is unclear.…”
Section: Extracorporeal Magnetic Stimulation Therapymentioning
confidence: 99%
“…[202][203][204] EMST, which uses currentchanging magnetic fields, allows the induction of electrical stimulation in the desired deep tissue. The mechanism of EMST in the S2-S3 dermatomes for constipation is unclear.…”
Section: Extracorporeal Magnetic Stimulation Therapymentioning
confidence: 99%
“…In patients with outlet-type constipation, including PD patients, the angle may not widen enough and the contrast will not be completely expelled (Fig. 3) [33,34]. This may be due to failure of the puborectalis muscle to relax.…”
Section: Defecographymentioning
confidence: 95%
“…133 Other studies reported non-significantly increased rectal volume, significantly increased residual volumes after defecation, and decreased rectal contraction in PD 128, 141 However, Edwards et al 127 found no significant increase in post-defecation residuals in mild-to-moderate stage PD cases in the off state. A small study showed that botulinum toxin injection in the puborectalis muscle was efficacious in decreasing tonus in the anorectal muscle and an improvement in the anorectal angle was also seen during straining.…”
Section: Functional Imaging Of the Gastrointestinal Tractmentioning
confidence: 99%